Process of cartographic generalization in maps digitalization - Minashkina Natalia; Valieva Albina; Ibraimova Aziza; Rakhimbabayeva Marhamat; Islamova Zulfiya (BIO Web of Conferences)
This article examines the results of a comparison of two methods of cartographic generalization when creating maps using the traditional method, i.e. “manually” and utilizing automated generalization techniques during computer-based map creation. Generalization is an essential characteristic of any map. Even the most detailed large-scale maps involve a degree of generalization, as representing every object with complete precision is impractical. This text explores the concept of automated cartographic generalization, highlighting its benefits and limitations, as well as the capabilities of computer technologies and specific software in the map-making process. Cartographic generalization creates certain accents and helps to show qualitatively new information on the map. Map compilation is the production of the original map, which involves creating a mathematical framework, incorporating content derived from cartographic materials with appropriate generalization, and finalizing the cartographic representation. The initial map compiler refers to the original map developed through this compilation process, on which the content elements are applied in accordance with the requirements of the editorial documents.